2022
DOI: 10.3390/polym14101981
|View full text |Cite
|
Sign up to set email alerts
|

PVA-Based Electrospun Biomembranes with Hydrolyzed Collagen and Ethanolic Extract of Hypericum perforatum for Potential Use as Wound Dressing: Fabrication and Characterization

Abstract: Biological, physicochemical, structural, and thermal properties of PVA-based electrospun wound dressings added with hydrolyzed collagen (HC) and different concentrations of Hypericum perforatum ethanolic extract (EEHP) were studied. Membrane characterization was carried out by X-ray diffraction, Fourier infrared spectroscopy, differential scanning calorimetry, barrier properties, scanning electron microscopy, image analysis (diameter and pore size), as well as antimicrobial and anti-inflammatory activities. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…By contrast, Kim et al [ 42 ] studied the attachment and serial proliferation rates of human prostate epithelial cells on electrospun polycaprolactone mats containing PVA, and the introduction of PVA increased the proliferation rate of the cells. In another study, fibroblasts were grown on PVA-based electrospun biomembranes; the results showed that PVA supported cell growth and proliferation [ 43 , 44 ]. In conclusion, PVA was chosen in combination with other materials as a barrier or facilitator layer for use as a GTR membrane to provide mechanical support and prevent rapid epithelial attachment or promote target cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Kim et al [ 42 ] studied the attachment and serial proliferation rates of human prostate epithelial cells on electrospun polycaprolactone mats containing PVA, and the introduction of PVA increased the proliferation rate of the cells. In another study, fibroblasts were grown on PVA-based electrospun biomembranes; the results showed that PVA supported cell growth and proliferation [ 43 , 44 ]. In conclusion, PVA was chosen in combination with other materials as a barrier or facilitator layer for use as a GTR membrane to provide mechanical support and prevent rapid epithelial attachment or promote target cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments were performed in independent triplicates. In this analysis, the denaturation temperature (TD), the decomposition temperature (TDS), the melting temperature (Tm) and the glass transition temperature (Tg) are reported [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…PVA with different drug formulations has been reported by various research groups for its wound-healing potential. A. García-Hernández et al reported PVA-based biomembranes with hydrolyzed collagen (HC) and ethanolic extract for their wound dressing characteristics [ 84 ]. Different concentrations of ethanolic extract of Hypericum perforatum ( EEHP ) in PVA/HC were evaluated.…”
Section: Electrospinning-based Pva Ddssmentioning
confidence: 99%